Stock Assessment of Squid (Loligo sp.) in Banten Bay, Banten Province : Kajian Stok Cumi-Cumi (Loligo sp.) di Perairan Teluk Banten, Provinsi Banten - Rurisca Kurnia Puspitasari; Achmad Fahrudin (Tropical Fisheries Management Journal, 2019)
Squid (Loligo sp.) is a fishery resource with important economic value and the second highest production rate landed in PPN Karangantu, Banten. The high fishing activity allows a decline in squid population in Banten Bay. The study aimed to examine the status stock of squid (Loligo sp.) In Banten Bay based on catch data landed in PPN Karangantu, Banten. The stock was suspected by Surplus Production Model using secondary data obtained from the PPN Karangantu included catch production and effort data of squid fisheries in 2010 to 2014. Based on the analysis of potential (MSY) of squids utilization are 76% or moderate exploited. These conditions indicate the squids resources have not experienced overfishing, yet its utilization has exceeded 50% of MSY. The catch and effort on squids at actual conditions are lower than the optimum effort (MSY), so that they can be increased up to 361.91 tons/year and 1083 trips/year.